2021
DOI: 10.1038/s41598-021-01614-7
|View full text |Cite|
|
Sign up to set email alerts
|

Sarcopenia risk and associated factors among Chinese community-dwelling older adults living alone

Abstract: Sarcopenia, defined as a progressive loss of muscle mass and reduced muscle strength and functional capacity, is common among older adults. This study aimed to assess the proportion of people at risk of sarcopenia and probable sarcopenia among Chinese community-dwelling older adults living alone and to identify the associated factors. A total of 390 older adults were included in this study. Sarcopenia and probable sarcopenia were defined according to the criteria of the Asian Working Group for Sarcopenia 2019.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 37 publications
5
36
1
Order By: Relevance
“…The most relevant factor was age, and the risk of sarcopenia was high in those aged 85 years or older. Sarcopenia occurs during aging and occurs with advancing age 13 According to a study of elderly aged 85 years 16 , a study of the elderly living alone in a Chinese community 33 , a study of elderly patients with osteoarthritis of the knee 34 , a study of the elderly over 70 years of age and a study of the elderly living in residence 18 , the prevalence of sarcopenia increased with age, supporting the results of this study. In terms of gender, the risk of sarcopenia was higher among elderly women than among men 16 .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The most relevant factor was age, and the risk of sarcopenia was high in those aged 85 years or older. Sarcopenia occurs during aging and occurs with advancing age 13 According to a study of elderly aged 85 years 16 , a study of the elderly living alone in a Chinese community 33 , a study of elderly patients with osteoarthritis of the knee 34 , a study of the elderly over 70 years of age and a study of the elderly living in residence 18 , the prevalence of sarcopenia increased with age, supporting the results of this study. In terms of gender, the risk of sarcopenia was higher among elderly women than among men 16 .…”
Section: Discussionsupporting
confidence: 63%
“…In particular, as a result of analyzing factors affecting muscle strength according to gender, older women were more stressed than men, perceived that they had a more obese body image, and had a lower quality of life 32 . In addition, this study found that obesity and physical activity had an effect on the sarcopenia in the elderly in China 33 . In order to prepare a plan for preventing sarcopenia in the elderly, nursing education and interventions should be devised to identify the exact physical condition of the elderly and to have a positive body image.…”
Section: Discussionmentioning
confidence: 59%
“…In our study, it was found that 26.7% of women at the age over 40 years old have a high risk of sarcopenia, and this index increases from 1.5% in the subjects at the age 40-49 years old to 73.7% in the females over 80 years old. In a study by Chinese colleagues, it was shown that among persons older than 60 years old (average age 78.1 ± 7.4 years), 57.7% had a high risk of sarcopenia [25]. In our study, this index was lower (39.3%), but the average age of our cohort was also lower.…”
Section: Discussioncontrasting
confidence: 64%
“…The main factors associated with sarcopenia also include low body weight [25,30]. A study conducted in Taiwan showed that a low BMI is one of the leading risk factors for sarcopenia, and its increase by 1 kg/m 2 signi cantly reduces the sarcopenia risk.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 19 studies were included in the final review. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] Twelve studies [43][44][45][52][53][54][55][56][57][59][60][61] were conducted in Asian countries such as China, 44,45,53,54,56 Thailand, 61 Japan 52,57,60 and Korea 59 and only four studies were conducted in non-Asian countries such as Brazil 46,48 and Colombia, 49,50 while three studies were conducted in a transcontinental country, Turkey. 47,51,58 All the research included were cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%